Economic Determinants of Audit Committee Independence - Klein, April (The Accounting Review, 2002)
This paper provides empirical evidence that audit committee independence is associated with economic factors. I find that audit committee independence increases with board size and board independence and decreases with the firm's growth opportunities and for firms that report consecutive losses. In contrast, no relation is found between audit committee independence and creditors' demand for accounting information. Although the analyses are based on data from 1991 to 1993, these results have implications for NYSE and NASDAQ listing requirements for audit committees adopted in December 1999. Specifically, the new requirements give firms the option of including non-outside directors on their audit committees if it is in the best interests of the firm to do so.